Accurate NMR Shieldings with σ-Functionals - Fauser, Steffen; Drontschenko, Viktoria; Ochsenfeld, Christian; Görling, Andreas (Journal of Chemical Theory and Computation, 2024)
In recent years, density-functional methods relying on a new type of fifth-rung correlation functionals called σ-functionals have been introduced. σ-Functionals are technically closely related to the random phase approximation and require the same computational effort but yield distinctively higher accuracies for reaction and transition state energies of main group chemistry and even outperform double-hybrid functionals for these energies. In this work, we systematically investigate how accurate σ-functionals can describe nuclear magnetic resonance (NMR) shieldings. It turns out that σ-functionals yield very accurate NMR shieldings, even though in their optimization, exclusively, energies are employed as reference data and response properties such as NMR shieldings are not involved at all. This shows that σ-functionals combine universal applicability with accuracy. Indeed, the NMR shieldings from a σ-functional using input orbitals and eigenvalues from Kohn-Sham calculations with the exchange-correlation functional of Perdew, Burke and Ernzerhof (PBE) turned out to be the most accurate ones among the NMR shieldings calculated with various density-functional methods including methods using double-hybrid functionals. That σ-functionals can be used for calculating both reliable energies and response properties like NMR shieldings characterizes them as all-purpose functionals, which is appealing from an application point of view.
CRIS-Team Scopus Importer:2024-07-19